2011
DOI: 10.1007/s00405-011-1515-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical features of human papillomavirus in head and neck squamous cell carcinoma in Okinawa, southern Japan

Abstract: Previous studies from Okinawa, a subtropical island in southern Japan, demonstrated a higher prevalence of human papillomavirus (HPV) in oral carcinoma and a higher incidence of oral and pharyngeal carcinoma than those for mainland Japan. The present study aims to investigate epidemiologic and clinical features of HPV in head and neck squamous cell carcinoma (HNSCC) in Okinawa. A total of 150 DNA samples from 150 Okinawan patients with head and neck squamous cell carcinoma (HNSCC) were screened for HPV sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 19 publications
4
48
1
Order By: Relevance
“…These varying results may be due to geographical and ethnical differences among studied populations, variation in origin of studied material, as well as different detection methods. Epidemiological studies have demonstrated differences in HPV prevalence among countries, reaching over 90% of HPV-positive OPSCC in Scandinavian countries [52][53][54] Additionally, HPV has a greater association with the oropharynx than with other subsites of the head and neck region, such as the oral cavity or larynx. 15 Thirteen studies included for review studied a mixture of subsites in the head and neck region, including the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…These varying results may be due to geographical and ethnical differences among studied populations, variation in origin of studied material, as well as different detection methods. Epidemiological studies have demonstrated differences in HPV prevalence among countries, reaching over 90% of HPV-positive OPSCC in Scandinavian countries [52][53][54] Additionally, HPV has a greater association with the oropharynx than with other subsites of the head and neck region, such as the oral cavity or larynx. 15 Thirteen studies included for review studied a mixture of subsites in the head and neck region, including the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Most publications in the literature are based on HPV 16 detection in surgical pathology specimens and use HPV detection methods such as PCR and ISH [6,7,8,9,10]. …”
Section: Discussionmentioning
confidence: 99%
“…Compared to oral carcinomas, a greater diversity of other HPV types has been detected: HPV18, HPV26, HPV31, HPV33, HPV39, HPV36, HPV45, HPV51, HPV52, HPV58, HPV59, HPV66, and HPV69 [8,9,14,20,26,29,39,65,71,90,94]. Low-risk HPV are uncommonly detected, and might represent incidental ''bystander'' rather than possibly ''driver'' infection [29,39,65,75,90,94].…”
Section: Hpv and Cancers Of The Larynxmentioning
confidence: 99%